A Molecular-Orbital Model for Amorphous Group IV Semiconductors - M. A. Grado-Caffaro; M. Grado-Caffaro (Active and Passive Electronic Components)
A theoretical model based on standard molecular-orbital theory and extended Hückel approach is proposed. This model is valid for amorphous group IV semiconductors and represents a substantial improvement of the state of the art.